Logistic outsourcing in pharmacy. the theory and practice - M. V. Bilous; O. P. Shmatenko; O. A. Ryzhov; T. S. Raikova; D. V. Drozdov (The State Expert Center of the Ministry of Health of Ukraine, 2018)
Today, the introduction and application of a logistics approach to resource management allows pharmaceutical companies to increase their social, environmental and economic efficiency. The article is aimed to research the essence of the concept, types and party of logistic outsourcing in practical pharmacy. To reach the aimreview of foreign and domestic scientific sources and the existing legal framework of Ukraine on this issue have been analyzed. Investigation methods were bibliographic and analytical ones. The results of these studies indicate the today outsourcing is one of the main logistics strategies of domestic pharmaceutical companies, which is actively used in the sphere of IT-technologies and warehouse services. At the same time for ensuring high-quality providing outsourcing services, a legal and regulatory framework is needed that standardizes the interaction between firm customer and the outsourcer, also the development of standards for the provision of services of a certain type of outsourcing. Wide introduction of logistics outsourcing, as a modern form of optimization of logistics business processes, requires the formation of professional competence among future pharmacists in pharmaceutical logistics, its tools and strategies, i.e. training of competitive professionals capable of working in various directions of practical pharmacy. Introduction of the topic «Logistic outsourcing in practical pharmacy» in the educational process of students of pharmaceutical faculties (university), pharmacists-interns and pharmacists at the postgraduate level of training is necessary. It will improve the theoretical and practical training of future specialist pharmaceutists and will allow them to apply the knowledge which would be gained in the future in logistics outsourcing in the activities of pharmaceutical companies.